Enhancement of Nonlinear Optical Scattering by Gold Nanoparticles through Aggregation‐Induced Plasmon Coupling in the Near‐Infrared. Issue 13 (11th June 2019) - de Coene, Yovan; Deschaume, Olivier; Zhang, Yuqing; Billen, Arne; He, Jing; Seré, Stephanie; Knoppe, Stefan; Van Cleuvenbergen, Stijn; Verbiest, Thierry; Clays, Koen; Ye, Jian; Bartic, Carmen
Abstract: Gold nanoparticles (AuNPs) are regarded as promising building blocks in functional nanomaterials for sensing, drug delivery and catalysis. One remarkable property of these particles is the localized surface plasmon resonance (LSPR), which gives rise to augmented optical properties through local field enhancement. LSPR also influences the nonlinear optical properties of metal NPs (MNPs) making them potentially interesting candidates for fast, high resolution nonlinear optical imaging. In this work we characterize and discuss the wavelength dependence of the hyper‐Rayleigh scattering (HRS) behavior of spherical gold nanoparticles (GNP) and gold nanorods (GNR) in solution, from 850 nm up to 1300 nm, covering the near‐infrared (NIR) window relevant for deep tissue imaging. The high‐resolution spectral data allows discriminating between HRS and two photon photoluminescence contributions. Upon particle aggregation, we measured very large enhancements (ca. 10 4 ) of the HRS intensity in the NIR, which is explained by considering aggregation‐induced plasmon coupling effects and local field enhancement. These results indicate that purposely designed coupled nanostructures could prove advantageous for nonlinear optical imaging and biosensing applications. Abstract : The wavelength dependence of the hyper‐Rayleigh scattering behavior of spherical gold nanoparticles and gold nanorods in characterized in silution from 850 to 1300 nm, covering the near‐infrared window relavant for deep tissue imaging.